The Role of Lower Airway Dysbiosis in Asthma: Dysbiosis and Asthma - Lu, Junying; Xiong, Lingxin; Zhang, Xiaohao; Liu, Zhongmin; Wang, Shiji; Zhang, Chao; Zheng, Jingtong; Wang, Guoqiang; Zheng, Ruipeng; Simpson, Jodie L.; Wang, Fang (Mediators of Inflammation, 2017)
With the development of culture-independent techniques, numerous studies have demonstrated that the lower airway is not sterile in health and harbors diverse microbial communities. Furthermore, new evidence suggests that there is a distinct lower airway microbiome in those with chronic respiratory disease. To understand the role of lower airway dysbiosis in the pathogenesis of asthma, in this article, we review the published reports about the lung microbiome of healthy controls, provide an outlook on the contribution of lower airway dysbiosis to asthma, especially steroid-resistant asthma, and discuss the potential therapies targeted for lower airway dysbiosis.